Familial primary gastric lymphoma. Issue 1 (January 1993) - Hayoz, D; Extermann, M; Odermatt, B F; Pugin, P; Regamey, C; Knecht, H
Abstract : Familial lymphoma is uncommon and is usually associated with various forms of hereditary immunodeficiencies. Primary gastric lymphomas that occurred in three adults from the same family, who had no overt immunodeficiency or cancer of non-lymphomatous origin, are reported. Two sisters presented with a low grade lymphoma of the mucosa associated lymphoid tissue type. Their father presented with a high grade form of later onset. All lymphomas have been phenotypically characterised as being of B cell origin. Epstein-Bar virus DNA was detected by polymerase chain reaction in the biopsy specimen of the high grade lymphoma but bcl-2/JH protooncogene rearrangement, t (14:18), was not identified in either the low or high grade lymphoma specimens tested.